Materials engineering and science : selected, peer reviewed papers from the International Conference on Materials Engineering and Science (IConMEAS 2018), August 08-09, 2018, Istanbul, Turkey - Dahham, Omar Sabbar; Zulkepli, Nik Noriman (Diffusion and defect data. Defect and diffusion forum, 2020)
This volume of the journal contains papers presented at the International Conference on Materials Engineering and Science (IConMEAS 2018), held at Istanbul, Turkey, August 08-09, 2018 and focuses on the research results in the field of materials science for various branches of industry and construction. Semiconductors, Nanostructures, Photonics, Optoelectronics, Polymers, Composites, Ceramics, Alloys, Biomaterials, Prosthesis, Building Materials, Properties Materials Science, Building Materials, Mechanical Engineering.